P809 The impact of different treatment strategies in newly diagnosed patients with Crohn's Disease: a multicentre study. (30th January 2023) - Revés, J; Morão, B; Montanaro, G; Sciberras, N; Bravo, A C; Glória, L; Ellul, P; Torres, J
Abstract: Background: The early use of effective therapy may change outcomes in patients with Crohn's disease (CD). The aim of this study was to compare three different treatment strategies in CD ("top-down", "accelerated step-up" and "regular step-up" therapy). Methods: This was a retrospective multicentre study including patients with incident CD between 2009-2021. Patients were categorized into 3 treatment groups: group 1) "top-down": anti-TNF ± immunomodulator (IM) within the first year of diagnosis with a maximum interval of 6 months between both drugs; group 2) "accelerated step-up": IM within the first year of diagnosis followed by anti-TNF 6-12 months later, and group 3) "regular step-up": IM within the first year of diagnosis with or without the need to further escalate to biologic (>12 months after the beginning of IM). The primary outcome was endoscopic healing (EH; SES-CD<3 and no ulcers) at the end of the follow-up; secondary outcomes were CD-related intestinal resection and hospitalization due to CD-flare. Cox regression analysis was performed and Kaplan-Meier curves were computed for each outcome. Results: 156 patients (54% males) were included, with 46% having ileocolonic disease (L3) and 68% an inflammatory phenotype (B1) at diagnosis. Baseline patients' characteristics in each different treatment strategy are demonstrated in Table 1. Patients were followed for a median of 69 (44-98) months; 12% in group 1 and 19% in group 2 had to switch biologicals (p=0.4); 64% in group 3 escalated to biologicals with a median time since diagnosis of 30 (20-50) months. In group 1, 73% of the patients used concomitant IM. At the end of follow-up, 50% of all patients achieved EH, 20% needed hospitalization and 13% had a CD-related intestinal resection. In a multivariate model adjusted for gender, age at diagnosis, disease location, disease behaviour, perianal disease, and prior surgery, patients in group 3 had a lower probability of achieving EH when compared with patients in group 1 (HR 0.7, 95%CI 0.5-0.96, p=0.02) and group 2 (HR 0.3, 95%CI 0.1-0.8, p=0.01). Kaplan-Meier curves are demonstrated in Figure 1. Using the same model, no differences were found in terms of hospitalization or need for intestinal surgery. Fistulizing disease was a significant predictor for intestinal surgery (HR 2.4, 95%CI 1.5-3.8, p<0.01). Conclusion: Introduction of biological therapy within the first two years of diagnosis, either in a "top-down" or "accelerated step-up" approach was associated with a higher probability of achieving EH, as compared to the introduction of an immunomodulator followed by a later introduction of biologic. No differences were found for hospitalization or intestinal surgery. Fistulizing disease was a significant predictor for surgical intervention.